Threonine 286 of fatty acid desaturase 7 is essential for ω-3 fatty acid desaturation in the green microalga Chlamydomonas reinhardtii - Lim, Jong-Min; Vikramathithan, Jayaraman; Hwangbo, Kwon; Ahn, Joon-Woo; Park, Youn-Il; Choi, Dong-Woog; Jeong, Won-Joong (Frontiers in Microbiology, 2015)
Omega-3 fatty acid desaturases catalyze the conversion of dienoic fatty acids (C18:2 and C16:2) into trienoic fatty acids (C18:3 and C16:3), accounting for more than 50% of the total fatty acids in higher plants and the green microalga Chlamydomonas reinhardtii. Here, we describe a Thr residue located in the fourth transmembrane domain of fatty acid desaturase 7 (FAD7) that is essential for the biosynthesis of ω-3 fatty acids in C. reinhardtii. The ω-3 fatty acid deficiency in strain CC-620, which contains a putative missense mutation at Thr286 of CrFAD7, was recovered by the overexpression of CC-125 CrFAD7. A Ser substitution in position 286 was able to partially complement the phenotype of the ω-3 fatty acid deficiency, but other substitution variants, such as Tyr, His, Cys, and Gly, failed to do so. Prediction of the phosphorylation target site revealed that Thr286 may be phosphorylated. Analysis of the structural conformation of CC-620 CrFAD7 via topology prediction (and bends in the helix) shows that this missense mutation may collapse the catalytic structure of CrFAD7. Taken together, this study suggests that Thr286 is essential for the maintaining the catalytic structure of CrFAD7.